ANALISIS KEBIASAAN BELAJAR SISWA TERHADAP HASIL BELAJAR DI BAWAH KKM PADA MATA PELAJARAN IPAS DI KELAS V SDN 106811 BANDAR SETIA - Yanti, Ezerina Devi; Simanjuntak, Sorta; Sitohang, Risma; Mailani, Elvi; Ananda, Lala Jelita (Jurnal Merah Putih Sekolah Dasar, 2024)
The purpose of this study was to analyze students' learning habits on learning outcomes in IPAS subjects regarding Chapter 5 learning material on How We Live and Grow in class V SDN 106811 Bandar Setia. The type of research used in this study is quantitative research with descriptive methods. The population of this study was the entire fifth grade of SDN 106811 Bandar Setia with a total of 28 students with a saturated sampling technique. The data collection technique was carried out by distributing 20 multiple choice questions and 24 item questionnaires with a Likert scale, while the analysis technique was descriptive statistics. The results of this study indicate that the analysis of student study habits is categorized as moderate with a value of 59.48%. This is evidenced from the value of student study habits in class V SDN 106811 Bandar Setia in the Delay Avoidant sub variable (readiness in learning) of 60.76% including in the high category and the Work Methods sub variable (work methods in learning) with a percentage value of 58.21% including in the medium category. Meanwhile, the data on student learning outcomes in IPAS subjects regarding Chapter 5 learning material on How We Live and Grow obtained an average result of 72.32 which is included in the œsufficient category. So it can be concluded that student learning habits are classified as moderate towards student learning outcomes below the KKM of class V SDN 106811 Bandar Setia.Keywords: Analysis of Student Study Habits, Learning Outcomes